Investigating the potential of fish oil as a nutraceutical in an animal model of early life stress. (1st February 2022) - Egerton, Sian; Donoso, Francisco; Fitzgerald, Patrick; Gite, Snehal; Fouhy, Fiona; Whooley, Jason; Dinan, Ted G.; Cryan, John F.; Culloty, Sarah C.; Ross, R. Paul; Stanton, Catherine
ABSTRACT: Background: Early life stress is a key predisposing factor for depression and anxiety disorders. Selective serotonin re-uptake inhibitors (SSRI) are frequently used as the first line of pharmacology treatment for depression but have several negative qualities, i.e. a delay or absence of effectiveness and negative side-effects. Therefore, there is a growing need for new nutraceutical-based strategies to blunt the effects of adverse-life events. Objectives: This study aimed to use the maternal separation model in rats to test the efficacy of fish oil dietary supplementation, on its own and in conjunction with the SSRI anti-depressant fluoxetine, as a treatment for depressive and anxiety-like symptoms associated with early life stress. Methods: Behavioural tests (open field test, elevated plus maze test and forced swim test) and biochemical markers (corticosterone, BDNF, brain fatty acids and short chain fatty acids) were used to analyse the effects of the dietary treatments. Gut microbial communities and relating metabolites (SCFA) were analysed to investigate possible changes in the microbiota-gut-brain axis. Results: Maternally separated rats showed depressive-like behaviours in the forced swim and open field tests. These behaviours were prevented significantly by fluoxetine administration and in part by fish oil supplementation. Associated biochemical changes reported include altered brain fatty acids, significantly lower plasma corticosterone levels (AUC) and reduced brain stem serotonin turnover, compared to untreated, maternally separated (MS) rats. Untreated MS animals had significantly lower ratios of SCFA producers such as Caldicoprobacteraceae, Streptococcaceae, Rothia, Lachnospiraceae_NC2004_group, and Ruminococcus_2, along with significantly reduced levels of total SCFA compared to non-separated animals. Compared to untreated MS animals, animals fed fish oil had significantly higher Bacteroidetes and Prevotellaceae and reduced levels of butyrate, while fluoxetine treatment resulted in significantly higher levels of Neochlamydia, Lachnoclostridium, Acetitomaculum and Stenotrophomonas and, acetate and propionate. Conclusion: Despite the limitations in extrapolating from animal behavioural data and the notable differences in pharmacokinetics between rodents and humans, the results of this study provide a further advancement into the understanding of some of the complex systems within which nutraceuticals and pharmaceuticals effect the microbiota-gut-brain axis.